Better than expected? Predictors of coping with expectation violations in the communication about death and dying - Bendel, Yannik; Gesualdo, Chrys; Pinquart, Martin; von Blanckenburg, Pia (Frontiers in Psychology, 2023)
Background: End-of-life (EOL) communication is often avoided, especially among young adults. Negative expectations concerning EOL conversations with relatives or significant others are one major reason. Objective: To investigate how best to violate negative expectations concerning EOL conversations by identifying predictors of coping with expectation violations in this context. Methods: Vignettes describing expectation violations in the context of EOL communication were presented to a sample of 261 university students. In a first experiment, the credibility of the expectation-disconfirming information was manipulated. In a second experiment, the valence of the disconfirming evidence was manipulated. As outcome measures, the subjective likelihood of two different responses to the expectation violation was assessed: (1) ignoring the disconfirming evidence (immunization) and (2) changing expectations (accommodation). Results: Overall, participants experiencing a worse-than-expected event showed more immunization (F(1, 257) = 12.15, p < .001, ηp = .05), while participants experiencing a better-than-expected event showed more accommodation (F(1, 257) = 30.98, p < .001, ηp = .11). Participants with higher fear of death (F(1, 257) = 12.24, p < .001, ηp = .05) as well as higher death avoidance tendencies (F(1, 257) = 17.16, p < .001, ηp = .06) showed less accommodation in response to a better-than-expected event. Conclusion: In general, young adults appear to update their expectations quickly in response to unexpectedly positive experiences in the context of EOL communication. However, individuals with higher fear of death and higher death avoidance tendencies appear to be at higher risk of maintaining negative expectations despite disconfirming evidence.